THE WAYS OF LEARNING PHRASEOLOGIZMS WITH LINGUISTIC COMPONENTS EXPRESSING CULTURAL MEANING IN TEACHING PROCESS (Journal of Universal Science Research, 2023)
Phraseological unity can come across sentence boundaries and even large parts of the text, specific sources of interdependence and associative connections of figurative and direct information. The linguistic nature of the phraseological unit has been comprehensively studied today. Indeed, knowledge of idioms is an important indicator of target language proficiency. Teaching and learning phrasal verbs helps to reveal the conative processes of the mind in creative thinking. At the same time, it helps to develop other language skills: speaking, reading, etc. Development in lexical, lexical and stylistic awareness can lead to the development of awareness, which includes the perception and development of changes in basic form a nd meaning. The purpose of this scientific article is to reveal phraseological unity, associative connections and stylistic projects, linguistic cohesion in the text and new meaning in the context through the essence of teaching phraseology.